Operational Performance Improvement Analysis Through Six Sigma Approach: Case Study at PT. Freight Express Surabaya - Pramudya Audrey Prienycha Islamey; Slamet Riyadi; Fausta Ari Brata (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aims to address operational inefficiencies at PT Freight Express Surabaya, specifically focusing on document delays and inter-divisional coordination issues. Employing the descriptive qualitative method with a case study approach through the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) framework, data was collected via observations, in-depth interviews, and historical shipment documentation. The results of the Measure phase indicate the company's baseline performance is at the 3.89 Sigma level with 8,241 Defects Per Million Opportunities (DPMO). The dominant issue identified through Pareto analysis is the lack of inter-divisional coordination. Root cause analysis (Analyze) using Fishbone and 5 Whys reveals that the primary failures stem from systemic failures in information transfer management and the absence of data validation at the source (quality at source). In the Improve phase, a Digital Gatekeeping strategy and formalization of communication protocols were formulated, projected to enhance performance to the 4.14 Sigma level. The Control phase emphasizes digital-based SOP standardization and real-time monitoring to ensure the consistency of improvements.